Efeito da estabilização de suspensões de sílica a eficiência de moagem em moinho agitador de esferas - Camargo, Willian Ferreira de (My University, 2019)
The milling of ceramic particles in water suspensions in stirred media mills is a high energy process indicated to obtain materiais in submicron and nanometric scales, and is presented as an alternative to chemical processes for powders synthesis. During milling, the particle size distribution, PSD, is shifted to smaller and smaller sizes. Electrostatic stabilization contrais the balance between repulsive and attractive forces and prevents agglomeration for particles under 1 µm. ln this work the particle size distribution evaluation for silica suspensions comminuted in stirred media mill was performed both in repulsive and attractive electrostatic interactions with the particles and the milling medium. The measurement of suspensions PSD and 􀀏 potential are imperative as measuring parameters for the evaluation of milling efficiency. Electroacoustic spectroscopy, dynamic light scattering and static light scattering were choosed for particle size characterization. During milling, samples of suspensions at different pH were analyzed at different times in order to monitor the sílica particles comminution. Measurements parameters for each characterization technique were changed in order to verify its effect in the measured PSD. lt was possible to observe that the results, obtained by the electroacoustic method, are dependent and sensitive to the variation in the suspension solids concentration. The results obtained by the static light scattering method indicated that the ultrasound application after addition of the sample generates perturbations in the PSD. The identification of the measurement limits for each experimental technique of PSD characterization was necessary to discern about the relative importance and effects of each parameter. The used particle size characterization techniques were not robust enough to state which pH enables the production of nanometric particles. The determination of the particles specific surface area was presented as an alternative technique to overcome the limitations of the prior used techniques, since the applicability of a nanometric powder can be measured by its surface reactivity. Volumetric and numerical distributions by AES and SLS provided lower equivalent diameters at pH 9, while DLS and SSA analysis by BET method indicated lower equivalent diameters, i.e., better milling efficiency at pH 5.
A moagem de partículas ceram,cas em suspensão em moinhos agitadores de esferas é um processo de alta energia indicado para a obtenção de materiais em escalas submicro e nanométricas e apresenta-se como alternativa em relação aos processos químicos de síntese de pós. Durante a moagem, a distribuição do tamanho de partícula, ou DTP, é deslocada para tamanhos cada vez menores. A estabilização eletrostática controla o balanço entre as forças repulsivas e atrativas e evita aglomeração das partículas abaixo de 1 µm. Neste trabalho foi realizada a avaliação da distribuição dos tamanhos de partícula de suspensões de sílica cominuídas em moinho agitador de esferas, em interações eletrostáticas repulsivas ou atrativas com o meio de moagem. A medição da DTP e potencial 􀀁 das suspensões são imperativos como parâmetros de medida para a avaliação da eficiência de moagem. A espectroscopia eletroacústica, o espalhamento de luz dinâmico e o espalhamento de luz estático foram as técnicas de caracterização de tamanho de partícula adotadas. Amostras de suspensões, com diferentes valores de pH durante a moagem, foram analisadas em tempos distintos, de modo a acompanhar a cominuição das partículas de sílica. Parâmetros importantes em cada técnica foram variados de modo a verificar o efeito causado na DTP. Foi possível observar que os resultados obtidos pelo método eletroacústico são dependentes e sensíveis à variação da concentração de sólidos da suspensão utilizada nas medições. Os resultados obtidos pelo método de espalhamento de luz estático indicaram que a aplicação de ultrassom após a adição da amostra gera perturbações na DTP. A identificação dos limites de medição de cada técnica experimental de caracterização da DTP fez-se necessário para discernir sobre a importância relativa e os efeitos de cada parâmetro. As técnicas de caracterização de tamanho de partícula utilizadas não foram robustas o suficiente para afirmar qual pH favorece a obtenção de partículas nanométricas. A determinação da área superficial específica das partículas apresentou-se como alternativa para suprir as limitações das técnicas anteriores, uma vez que a aplicabilidade de um pó nanométrico pode ser medida pela sua reatividade superficial. As distribuições volumétricas e numéricas por AES e SLS forneceram diâmetros equivalentes menores em pH 9, enquanto que as análises por DLS e da SSA pelo método BET indicaram menores diâmetros equivalentes e, portanto, melhor eficiência de moagem em pH 5.
Keywords: Sílica; Material cerâmico - Moagem; Partículas (Física, química, etc.); Silica; Ceramic materials - Milling; Particles